Challenges and opportunities for managing pediatric central nervous system tumors in China - Pak‐Yin Liu, Anthony (Pediatr Investig, 2020)
Central nervous system (CNS) tumors represent the most deadly cancer in pediatric age group. In China, thousands of children are diagnosed with CNS tumors every year. Despite the improving socioeconomic status and availability of medical expertise within the country, unique challenges remain for the delivery of pediatric neuro‐oncology service. In this review, we discuss the existing hurdles for improving the outcome of children with CNS tumors in China. Need for precise disease burden estimation, lack of intra‐ and inter‐hospital collaborative networks, high probability of treatment abandonment, along with financial toxicities from treatment represent the key challenges that Chinese healthcare providers encounter. The tremendous opportunities for advancing the status of pediatric neuro‐oncology care in and beyond the country are explored.